Odpowiedzialność nieletnich w Odrodzonej Rzeczpospolitej - Śliwonik, Szymon (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
This article discusses the issue of juvenile legal and criminal liability in the inter-war period and during the Second World War. Particular attention is paid to the issue of reactions criminal acts committed by juveniles on the grounds of the regulations of the 1932 Penal Code. The paper offers a complex presentation of said solutions implemented in the Second Republic of Poland’s penal system.
Keywords: criminal law; juvenile law; juvenile delinquency; criminal responsibility; Penal Code of 1932; reborn Republic of Poland